Preparation of high-activity coal char-based catalysts from high metals containing coal gangue and lignite for catalytic decomposition of biomass tar. (19th April 2021) - Du, Shilin; Dong, Yichen; Guo, Feiqiang; Tian, Beile; Mao, Songbo; Qian, Lin; Xin, Chengyun
Abstract: The potential of using high metals containing coal gangue and lignite to prepare high-activity coal char-based catalysts is investigated for effective biomass tar decomposition. Loose structure and rough surface are formed for these char-based catalysts with heterogeneous distribution of a large number of inorganic particles. In the biomass tar decomposition, the performance of the coal char-based catalysts is significantly influenced by the content of the metals in the raw materials and coal gangue char (GC) with the ash content as high as 50.80% exhibits the highest activity in this work. A high biomass tar conversion efficiency of 93.5% is achieved at 800 °C along with a significant increase in the fuel gas product. During the five-time consecutive tests, the catalytic performance of GC increases a little at the second or third times reuse and remains relatively stable, showing the remarkable stability of the catalyst in biomass tar decomposition applications. Graphical abstract: Image 1 Highlights: High-activity coal char-based catalysts were prepared for tar decomposition. The tar conversion efficiency reached 93.5% at 800 °C using GC catalyst. The inherent metal oxides on the catalyst exhibited high catalytic activity. The GC catalyst showed excellent stability during the five-time consecutive tests.